2008
DOI: 10.1159/000151508
|View full text |Cite
|
Sign up to set email alerts
|

Haplotype Analysis of the NADPH Oxidase p22<sup>phox</sup> Gene in Patients with Bronchial Asthma

Abstract: Background: Superoxide produced by airway epithelial and inflammatory cells may contribute to the pathogenesis of asthma. NADPH oxidase (an enzyme complex made up of 5 subunits) is a major source of superoxide in cells. We sought to elucidate the role of genetic variability in the gene encoding the p22phox subunit of the NADPH oxidase (CYBA, 16q24.3) in asthma susceptibility by means of an association study of haplotypes based on 3 common single nucleotide polymorphisms (SNPs), –930A/G, 242C/T (H72Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 61 publications
(38 reference statements)
1
7
0
Order By: Relevance
“…In particular, we confirmed a potential role in the pathogenesis of asthma for CYBA and CAT genes that was associated with asthma in Czech [60] and Canadian [61] populations, respectively. In addition, the associations of asthma with the IL5 C-703T polymorphism in Russians from the city of Tomsk [35] and IL1B −511C>T in the Canadian Asthma Primary Prevention Study [62] have been successfully replicated in our study.…”
Section: Discussionsupporting
confidence: 68%
“…In particular, we confirmed a potential role in the pathogenesis of asthma for CYBA and CAT genes that was associated with asthma in Czech [60] and Canadian [61] populations, respectively. In addition, the associations of asthma with the IL5 C-703T polymorphism in Russians from the city of Tomsk [35] and IL1B −511C>T in the Canadian Asthma Primary Prevention Study [62] have been successfully replicated in our study.…”
Section: Discussionsupporting
confidence: 68%
“…24,39,40 NOX2 gene polymorphism, which may affect the production of ROS by leukocytes, is associated with different human diseases, including asthma, arthritis, stroke, and coronary artery disease. [41][42][43][44] It was recently reported that lack of NADPH oxidase activity markedly increased the severity of arthritis in a mouse model of arthritis. 45 How leukocyte NADPH oxidase contributes to tissue oxidant stress and regulates or facilitates inflammation in different tissue types is, therefore, an important question to ask if we are to elucidate the pathogenesis of these diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Compound 4-(2-Aminoethyl) benzene sulfonyl fluoride hydrochloride (AEBSF) is an irreversible serine protease inhibitor with broad specificity (trypsin, chymotrypsin, plasmin, thrombin, kallikreins) and high affinity. AEBSF is a unique molecule that can inhibit serine proteases as well as NADPH oxidase, the primary enzyme responsible for catalyzing the production of reactive oxygen species in epithelial cells, inflammatory cells, and phagocytes 5. Due to these properties, we hypothesized that AEBSF might reduce allergic airway inflammation.…”
Section: Introductionmentioning
confidence: 99%